Signs of the Sahara engraved in the context of animals’ representations and the beginnings of West African metallurgy - (:unkn) unknown (My University, 1994)
Engravers belonging to a society with a strong tradition of cattle breeding produced hundreds of abstract signs, together with representations of animals, bent metal objects and single shaft chariots, at the summit of a mountain in the Adrar des Iforas range in the Southern Sahara, Northern Mali. The comparison of these engravings with others found in regions to the north suggests that the north-western part of the African continent was affected by the symbolism of metal works from the Western and Eastern mediterranean areas in the IInd millenium bc.
Keywords: African Research